Salt Stress Triggers Phosphorylation of the Arabidopsis Vacuolar K(+) Channel TPK1 by Calcium-Dependent Protein Kinases (CDPKs) - Latz, Andreas (2012)
14–3–3 proteins play an important role in the regulation of many cellular processes. The Arabidopsis vacuolar two-pore K(+) channel 1 (TPK1) interacts with the 14–3–3 protein GRF6 (GF14-λ). Upon phosphorylation of the putative binding motif in the N-terminus of TPK1, GRF6 binds to TPK1 and activates the potassium channel. In order to gain a deeper understanding of this 14–3–3-mediated signal transduction, we set out to identify the respective kinases, which regulate the phosphorylation status of the 14–3–3 binding motif in TPK1. Here, we report that the calcium-dependent protein kinases (CDPKs) can phosphorylate and thereby activate the 14–3–3 binding motif in TPK1. Focusing on the stress-activated kinase CPK3, we visualized direct and specific interaction of TPK1 with the kinase at the tonoplast in vivo. In line with its proposed role in K(+) homeostasis, TPK1 phosphorylation was found to be induced by salt stress in planta, and both cpk3 and tpk1 mutants displayed salt-sensitive phenotypes. Molecular modeling of the TPK1-CPK3 interaction domain provided mechanistic insights into TPK1 stress-regulated phosphorylation responses and pinpointed two arginine residues in the N-terminal 14–3–3 binding motif in TPK1 critical for kinase interaction. Taken together, our studies provide evidence for an essential role of the vacuolar potassium channel TPK1 in salt-stress adaptation as a target of calcium-regulated stress signaling pathways involving Ca(2+), Ca(2+)-dependent kinases, and 14–3–3 proteins.